A general scenario to evaluate evolution of grassland birds in the Neotropics. (4th December 2020) - Norambuena, Heraldo V.; Van Els, Paul
Abstract : Neotropical grassland birds are intimately tied to their habitat and form a phylogenetically diverse group that has been poorly studied from an evolutionary point of view. Here we present a brief review of the biogeographical history of Neotropical grasslands of relevance to grassland birds. Based on this review, we have formulated the most relevant hypotheses related to the diversification and evolution of Neotropical grassland birds. Several of the hypotheses tested are complementary to those that can be tested for forest birds and may offer the researcher fruitful foci of study for assessing the role of South American geological evolution in shaping the diversification of the world's most diverse avifauna.